The economic contribution of farmer cooperatives for the state of Kansas - Clymer, Amanda Marie (Kansas State University, 2019)
Farmer cooperatives have contributed to the vitality and sustainability of many communities across rural America. Since the passage of the Capper-Volstead Act in 1922, cooperatives have not only served the needs of members, but also provided economic support, employment, and wages in rural communities. The objective of this research is to measure the total economic contribution of grain and farm supply cooperatives to the Kansas economy. Economic contribution results are often calculated utilizing the Input-Output and/or Social Accounting Matrix framework. IMPLAN, an economic analysis software, provides necessary data and the framework to quantify economic and employment contributions. The software enables total contribution to include the direct effects of farmer cooperatives, the indirect effect of the industry’s economic relationships, and the additional spending of wages and income by households and governments. This analysis utilized survey results of Kansas cooperatives, the CoBank Risk Analyst database, and the Kansas Department of Labor’s quarterly census of employment and wages. Modeling considered both local ownership and single-level taxation, two characteristics of cooperative businesses. Two economic contribution analyses depict industry variation based on degree of local ownership. The sample of cooperative survey respondents confirm a relatively high level of Kansas ownership. The actual contribution of the Kansas cooperative sector is likely closer to the upper bound total contribution results. The total direct, indirect, and induced results for the Kansas cooperative sector assuming completely localized ownership includes 9,940 jobs, $631.7 million in labor income, $1.1 billion in total income and $1.8 billion in output. Valuing the economic contribution of cooperatives to the Kansas economy can provide useful insights into the industry and its contribution to rural economic welfare. As consolidation and rapid growth has characterized the grain marketing and farm supply cooperative landscape, the results can inform discussion related to market influence, community support, and public policy.
Keywords: Cooperative; Kansas; Economic Contribution